2022
DOI: 10.1002/ece3.8495
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory in a changing climate—Effects of plant genotype and experimentally induced variation in plant phenology on two summer‐active lepidopteran herbivores and one fungal pathogen

Abstract: With climate change, spring warming tends to advance plant leaf‐out. While the timing of leaf‐out has been shown to affect the quality of leaves for herbivores in spring, it is unclear whether such effects extend to herbivores active in summer. In this study, we first examined how spring and autumn phenology of seven Quercus robur genotypes responded to elevated temperatures in spring. We then tested whether the performance of two summer‐active insect herbivores (Orthosia gothica and Polia nebulosa) and infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Chemical ecology temperatures are causing winter to become shorter in some geographical regions, with frost occurring later in the season (Loe et al, 2021;Sparks & Menzel, 2002;Williams et al, 2015) and leaf herbivory extending into early autumn (Gallinat et al, 2015;Loe et al, 2021;Zani et al, 2020), such as with caterpillars, leaf miners, and gall wasps (Ekholm et al, 2019(Ekholm et al, , 2022. For example, Lemoine et al (2014) found that the feeding rates of 11 herbivoreplant pairs (e.g., Atteva aurea and Ailanthus altissima, Danaus plexippus and Asclepias syriaca, among others) increased with warming temperatures.…”
Section: T a X O N O M Y C L A S S I F I C A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical ecology temperatures are causing winter to become shorter in some geographical regions, with frost occurring later in the season (Loe et al, 2021;Sparks & Menzel, 2002;Williams et al, 2015) and leaf herbivory extending into early autumn (Gallinat et al, 2015;Loe et al, 2021;Zani et al, 2020), such as with caterpillars, leaf miners, and gall wasps (Ekholm et al, 2019(Ekholm et al, , 2022. For example, Lemoine et al (2014) found that the feeding rates of 11 herbivoreplant pairs (e.g., Atteva aurea and Ailanthus altissima, Danaus plexippus and Asclepias syriaca, among others) increased with warming temperatures.…”
Section: T a X O N O M Y C L A S S I F I C A T I O Nmentioning
confidence: 99%
“…Such interactions are relevant because insects can be active during the non‐growing season (i.e., autumn and winter), such some leafhoppers (Stinson & Brown, 1983 ), sawflies (Kause et al., 2001 ), and larvae of leaf‐mining moths (Connor et al., 1994 ), which re‐appear with a second generation during late summer and/or consume leaves until senescence occurs in mid to late autumn (Connor et al., 1994 ). Furthermore, warming temperatures are causing winter to become shorter in some geographical regions, with frost occurring later in the season (Loe et al., 2021 ; Sparks & Menzel, 2002 ; Williams et al., 2015 ) and leaf herbivory extending into early autumn (Gallinat et al., 2015 ; Loe et al., 2021 ; Zani et al., 2020 ), such as with caterpillars, leaf miners, and gall wasps (Ekholm et al., 2019 , 2022 ). For example, Lemoine et al.…”
Section: Introductionmentioning
confidence: 99%